Numerical analysis of microwave heating cavity: Combining electromagnetic energy, heat transfer and fluid dynamics for a NaY zeolite fixed-bed. (5th June 2019) - Nigar, H.; Sturm, G.S.J.; Garcia-Baños, B.; Peñaranda-Foix, F.L.; Catalá-Civera, J.M.; Mallada, R.; Stankiewicz, A.; Santamaría, J.
Graphical abstract: Highlights: Electromagnetic, heat transfer and fluid dynamics coupled for MW heating simulation. Dielectric properties of NaY zeolite measured as a function of temperature 298–623 K. Temperature evolution and distribution results validated with experimental data. Model predicts thermal runaway of zeolite under MW heating. Abstract: Three-dimensional mathematical model was developed for a rectangular TE10n microwave heating cavity system, working at 2.45 GHz. Energy/heat, momentum equations were solved together with Maxwell's electromagnetic field equations usingComsol Multiphysics® simulation environment. The dielectric properties, ε' and ε'', of NaY zeolite (Si/Al = 2.5) were evaluated as a function of temperature. Considering these values, the microwave heating of a porous fixed-bed made of dry NaY zeolite was simulated. Electric field distribution, axial and radial temperature profiles and temperature evolution with time were obtained. The zeolite fixed bed was heated up to 180 °C in 5 min, with 30 W power. The fixed-bed temperature evolution under non-steady state conditions showed the same trend as the one observed experimentally with only an average deviation of 10.3%. The model was used to predict microwave heating of other materials improving energy efficiency of the microwave cavity. Furthermore, the developed model was able to predict thermal runaway for zeolites.